THERMOGENIC RESPIRATION IN MITOCHONDRIA OF SOME ANIMALS (Scientific journal of the Fergana State University, 2024)
In mitochondria of skeletal muscles of warm-blooded animals, two forms of respiration intensively function - coupled and uncoupled with ATP synthesis. In the cold-blooded animals, the uncoupled form of respiration is less developed.  High-uncoupled respiration in mitochondria, considered as thermogenic, as well as efficiency, reducing the metabolic mechanism in warm-blooded organisms.